PROBLEMS AND WAYS TO IMPROVE CORPORATE GOVERNANCE AT THE LEVEL OF JOINT-STOCK ENTERPRISES OF THE ENERGY COMPLEX UZBEKISTAN - Murodullayev, Feruzbek Ulugbek ugli (Educational Research in Universal Sciences, 2023)
In this article, we will talk about the problems in electricity and how to solve these problems from the roof of the corporate government in our country.